Leaf and hexagonal grid designs for lead-acid battery. An EIS analysis. (1st December 2022) - Calborean, Adrian; Bruj, Olivia; Morari, Cristian
Abstract: This work explore the fabrication of two distinct metallic grid architectures of positive electrode, namely hexagonal and leaf shapes, within the aim of improving the economic and the qualitative electrical performance aspects of lead-acid batteries in the automotive industry. By following a well-established aging procedure, Electrochemical Impedance Spectroscopy has been employed for their characterization by using different grid-acidic electrolyte interface changes. Two particular, parameters were investigated in order to predict the evolution of batteries lifetime performance: the resonance frequency single parameter, and time-dependent analysis of Constant Phase Element at 75 % State of Charge. Single resonance frequency fluctuations have been monitored at each PEIS step, in which we plotted the imaginary part of the impedance as function of frequency. An performance of battery lifetime has resulted for leaf battery than for hexagonal model, by comparison of the exponential-like increment degradation curve vs cycle number at SoC = 100 %. By using the effect of Q1 linear decay in the equivalent Randle circuit at 75 % SoC, we obtained for both models a smooth trend of the linear decay slopes, in particular in the second part of their lifetime, in agreement with previous investigated cells, demonstrating that is a robust feature, present in all fabricated cells. A fitting linear regression analysis depending on cycle number was applied to both batteries, in order to highlight the degradation grade of these curves. Another linear fit calibration of the degradation speed was applied for the second sector of batteries lifetime, pointing out a positive correction for the Q1 linear decay with ∼30 % for leaf cell over the hexagonal model, but less than previous investigated rectangular models or the industrial type. This suggests that the current homogeneity on the rectangular models during the charge-discharge processes is better distributed in the lower and upper parts of the plates than for hexagonal or leaf electrodes, being spotted here by the effect of current uniformity on their Randle circuit. The homogeneity of the electric field is not ensured by the shape of individual sectors, rather by their size and orientation. Highlights: We designed and fabricated positive electrode prototypes with hexagonal and leaf shape designs. EIS data through Randle circuit was used to analyze differences in homogeneity of the current distribution. A controlled aging of the battery has been used to find a correlation between Randles CPE parameters and battery's SoH. The extrapolation of data for CPE at 75 % can be used to predict battery lifetime. Single parameter resonance frequency can predict the speed degradation.